RATIONALITY ASSESSMENT OF ZINC FORMULATIONS AVAILABLE IN INDIA - Chary, Krishnan Vengadaragava; Bhaskaran, Rithu (International Journal of Pharmacy and Pharmaceutical Sciences, 2017)
Objective: To critically analyze the essentiality and irrational zinc preparations available in Indian market. Methods: This was conducted as cross-sectional analysis by department of pharmacology of our tertiary care hospital between June and December 2016. Data regarding various formulations of zinc were retrieved from current index of medical sciences and drug India database. Rationality assessment was done using prescribed guidelines and approved formulations of zinc by Central drug standard control organisation. Essentiality was checked using National list of essential medicine India, 2013 and latest version of WHO list essential medicine bulletin. Dosage regulation was assessed using Indian pharmacopeia guidelines, National institute of nutrition, India recommendation and upper daily intake toxicity intake, United States of America (USA) Results: Our study results showed wide variation in the number of zinc preparation. Total number of formulation available in the market is 335. Among zinc preparation, the preparation that contains 20 mg of zinc as recommended by various guidelines is 10 in number. About 325 preparations of zinc are added with one or more nutraceuticals. None of these fixed dose combination of zinc containing preparation is recommended as essential fixed regimen. Conclusion: Zinc has lot of relevance in treating recurrent diarrhoeal illness, especially in paediatric cases; however legal, regulatory and educational measures should be followed to curtail all the irrational zinc prescription development, promotion, marketing and prescription.